Analisis Bibliometrik Penelitian Mangrove di Indonesia dan Peluang Integrasi dengan SDGs (Jurnal Kemaritiman: Indonesian Journal of Maritime, 2025)
Mangrove ecosystems support biodiversity, climate change mitigation, and coastal community livelihoods, making them highly relevant to the Sustainable Development Goals (SDGs). However, a systematic understanding of how mangrove-related research in Indonesia aligns with the SDGs remains limited. This study aims to analyze the bibliographic trends in scientific publications using the keywords “mangrove” and “Indonesia” from 2015 to 2025 to explore dominant research themes and their connection to the SDGs framework. A bibliometric analysis was conducted using data extracted from Scopus-indexed publications. VOSviewer software generated a co-occurrence map of keywords and identified thematic clusters. The study revealed that research on mangroves in Indonesia predominantly falls within the fields of Agricultural and Biological Sciences (33.74%) and Environmental Science (24.76%), with emerging contributions from Biochemistry, Earth Sciences, and Social Sciences. Dominant keywords include “mangrove ecosystem,” “biodiversity,” “carbon stock,” “remote sensing,” and “restoration.” However, further analysis showed that these keywords, although thematically related to SDGs, especially Goals 13 (Climate Action), 14 (Life Below Water), and 15 (Life on Land), do not explicitly use SDG-related terminology. Clusters such as “carbon stock,” “fisheries,” and “climate change mitigation” exist in isolation, indicating a gap in conceptual integration with SDGs. This suggests that while mangrove research in Indonesia addresses components of sustainability, its alignment with the SDGs is still implicit. Therefore, this study highlights the need for future research to adopt a more integrative approach that explicitly connects mangrove studies with specific SDG targets to enhance policy relevance and impact.